Clinical Evaluation of Dental Implants with a Double Acid-Etched Surface Treatment: A Cohort Observational Study with Up to 10-Year Follow-Up - Juan Santos Marino (MDPI AG, 2021)
Background and objectives: The main purpose of this study was to evaluate the survival and success rates of dental implants with a double acid-etched surface treatment with evaluation times up to 10 years post-loading. Materials and Methods: This study was conducted at a hospital oral surgery and implantology unit. It included 111 dental implants with a double acid-etched surface. Three groups were created: Group 1 (1–3 years loading), Group 2 (3–5 years loading), and Group 3 (over 5 years loading). Probing depth, resonance frequency analysis (ISQ value), and marginal bone loss were evaluated. Results: The data obtained underwent statistical analysis. Overall, 78 patients were included in the study, who received, in total, 111 dental implants, all replacing single teeth. Mean probing depth was 3.03 mm and mean ISQ was 65.54. Regarding marginal bone loss, in Group 1, 67.6% of implants did not undergo any thread loss, in Group 2, 48.3%, and in Group 3, 59.6%; 59.10% of all implants did not present thread loss with a mean bone loss of 0.552 mm. The implant survival rate was 99.1%, and the success rate was 96.37%. Conclusions: Implants with a double acid-etched surface showed excellent success rates in terms of marginal bone loss, ISQ, and probing depth after up to 10 years of loading, making them a clinically predictable treatment option. Future studies are needed to compare this implant surface with other types in different restorative situations.